Sensory input, sex and function shape hypothalamic cell type development - Harris S. Kaplan; Brandon L. Logeman; Kai Zhang; Tate A. Yawitz; Celine Santiago; Noor Sohail; Mustafa Talay; Changwoo Seo; Serhiy Naumenko; Shannan J. Ho Sui; David D. Ginty; Bing Ren; et al. (Nature, 2025)
Abstract Mammalian behaviour and physiology undergo major changes in early life. Young animals rely on conspecifics to meet their needs and start showing nutritional independence and sex-specific social interactions at weaning and puberty, respectively. How neuronal populations regulating homeostatic functions and social behaviours develop during these transitions remains unclear. We used paired transcriptomic and chromatin accessibility profiling to examine the developmental trajectories of neuronal populations in the hypothalamic preoptic region, where cell types with key roles in physiological and behavioural control have been identified 1–6 . These data show a marked diversity of developmental trajectories shaped by the sex of the animal, and the location and behavioural or physiological function of the corresponding cell types. We identify key stages of preoptic development, including early diversification, perinatal emergence of sex differences, postnatal maturation and refinement of signalling networks, and nonlinear transcriptional changes accelerating at the time of weaning and puberty. We assessed preoptic development in various sensory mutants and find a major role for vomeronasal sensing in the timing of preoptic cell type maturation. These results provide new insights into the development of neurons controlling homeostatic functions and social behaviours and lay ground for examining the dynamics of these functions in early life.